WEBSITE PEMBELAJARAN ALGORITMA DENGAN VISUALISASI: KASUS JALUR LABIRIN DENGAN ALGORITMA PATHFINDING - Suwarno, Suwarno; Pratama, Jimmy; Vendryan (ZONAsi: Jurnal Sistem Informasi, 2024)
Understanding pathfinding algorithms is crucial for programmers. Pathfinding algorithms have been applied in many domains, including robotics, network routing, video game, and GPS. Computer science students are taught this pathfinding algorithm in their classes. Without concrete examples, algorithms have always been an abstract idea that is challenging to understand. Based on this, the research developed a website for the pathfinding algorithm visualization using the ADDIE method, which visualizes the maze's completion by employing the Breadth First Search, Depth First Search, and A* search. Subsequently, study was conducted utilizing the UTAUT model to analyze the components that motivate students to utilize the website. The study found that factors such as ease of use and comfort when using a pathfinding website's visualization algorithm increase students' willingness to use it and social factors have no influence on students.